2017
DOI: 10.1038/s41598-017-14296-x
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinizing oil in water and its removal via bacteria inhabiting the gels

Abstract: When crude oil samples were shaken (200 rpm) in seawater samples from the Arabian Gulf at 30 °C, usually oil-gels were produced spontaneously leaving the water quite clear. The gelators could probably be based on cholesteryl derivatives. Microscopic examination of the established gels revealed nanofibrellar structures similar to those described by earlier workers for artificially synthesized gelators. Communities of bacteria including prosthetic and stalked members as well as oil-degrading bacteria were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Furthermore, the unusual features of the MC-252 spill, i.e., its occurrence in deep water and extensive subsurface dispersant treatment leading to a deep-water plume of highly dispersed oil, make it highly likely that some MOS formed below the photic zone. For example, it is known that hydrocarbondegrading enrichments in the dark (Baelum et al, 2012) as well as pure cultures of hydrocarbon-degrading bacteria (Alcanivorax borkumensis, Omarova et al, 2019;Marinobacter hydrocarbonoclasticus, Vaysse et al, 2011;Halomonas sp., Gutierrez et al, 2013b; and Alteromonas sp., Gutierrez et al, 2018), can form EPS-rich films around oil droplets, sometimes creating flocs (Gutierrez et al, 2013a(Gutierrez et al, ,b, 2018, even causing gelation (Radwan et al, 2017), and microbial coatings on oil droplets will alter their surface properties and may result in reduced coalescence (Omarova et al, 2019). Unfortunately, the oil concentrations used in many of these studies were very high (up to 5,000 ppm), and nutrient levels were often many orders of magnitude above those available in the open sea (Bejarano et al, 2014;Wade et al, 2016), so it is not clear how well they mimic what happens in the ocean.…”
Section: Mechanisms Of Mos Formationmentioning
confidence: 99%
“…Furthermore, the unusual features of the MC-252 spill, i.e., its occurrence in deep water and extensive subsurface dispersant treatment leading to a deep-water plume of highly dispersed oil, make it highly likely that some MOS formed below the photic zone. For example, it is known that hydrocarbondegrading enrichments in the dark (Baelum et al, 2012) as well as pure cultures of hydrocarbon-degrading bacteria (Alcanivorax borkumensis, Omarova et al, 2019;Marinobacter hydrocarbonoclasticus, Vaysse et al, 2011;Halomonas sp., Gutierrez et al, 2013b; and Alteromonas sp., Gutierrez et al, 2018), can form EPS-rich films around oil droplets, sometimes creating flocs (Gutierrez et al, 2013a(Gutierrez et al, ,b, 2018, even causing gelation (Radwan et al, 2017), and microbial coatings on oil droplets will alter their surface properties and may result in reduced coalescence (Omarova et al, 2019). Unfortunately, the oil concentrations used in many of these studies were very high (up to 5,000 ppm), and nutrient levels were often many orders of magnitude above those available in the open sea (Bejarano et al, 2014;Wade et al, 2016), so it is not clear how well they mimic what happens in the ocean.…”
Section: Mechanisms Of Mos Formationmentioning
confidence: 99%
“…Spilled oil is removed, either by physical and chemical means, for example, land-filling and incineration (Kuiper, Lagendijk, Bloemberg, & Lugtenberg, 2004) or using catabolic activities of microorganisms, that is, bioremediation (Atlas, 1991;Atlas & Bartha, 1998;Piskonen & Itävaara, 2004). A recent study in our laboratory has shown that spilled oil could be removed physically by gelatinization, and that bacteria naturally inhabiting the produced gels could biodegrade the oil (Radwan, Al-Mailem, & Kansour, 2017). Unlike bioremediation, physical and chemical means are neither cost-effective nor always eco-friendly (Rosenberg, 1993).…”
mentioning
confidence: 99%